PENAL MEDIATION BY POLICE INSTITUTIONS IN HANDLING MIDDLE CRIMES IN REALIZING RESTORATIVE JUSTICE PRINCIPLES - Aisyah Muda Cemerlang; Heni Siswanto (PRANATA HUKUM, 2021)
Police duties as law enforcement has always put forward the principle of formal legality in an investigation. The investigators in performing their duties have a doubt in determining whether a case can be continued or not if a conciliation has been met. The problems of this research are to determine the implementation of mediation by the police in handling minor crime as an effort to realize restorative justice and to find out the inhibiting factors of the application of mediation by police in the effort to realize subtantive justice. The police officers in Bandar Lampung often encountered cases where conciliation was finally made so that the victim revoke the report; thus, the investigators tried to put forward the importance of justice and expediency; while the inhibiting factors included: First, the absence of a legal rule concerning penal mediation in criminal cases. Second, there was a gap in the application of mediation by the officers. Third, the police officers were too firm in applying the formal legal principles. It is suggested that the police officers need to emphasize the application of progressive law by applying restorative justice through the authority of discretion. It is necessary to have a perception adjustment in implementing the principle of restorative justice. Further, it is important to implement a rule regarding mediation as a settlement of criminal cases.